(untitled) - Jennings, Marianne (Mason, Ohio, 2006)
The text provides superior legal, ethical, and regulatory coverage while fully integrating practical business practices for tomorrow's business managers. Legal topics are explored and explained through real-world business examples (over 300 references to business are made in the text). In addition to a solid foundation in the law, students learn valuable legal and ethical reasoning skills through a variety of critical thinking exercises. Students receive -- and appreciate -- practical advice on when it is necessary to call a lawyer, how best to use legal aid services and how to avoid legal trouble in the first place
Keywords: Đạo đức kinh doanh,Business law,Business ethics,Luật thương mại; Hoa Kỳ; United States